SWAT based GIS modelling and impact assessment of dam project in Karkheh river basin and wetland using spatio-temporal satellite data - Ghobadi, Yasser (2015)
Water shortages in the arid parts of the world are affecting the human welfare, economic activity, and political stability of these areas. Faced with overpopulation problems and demand for development of new agricultural lands to support increasing population, many countries of the arid world are adopting aggressive policies to develop new agricultural communities without careful analysis of the environmental and hydrologic impacts of these projects. Dust storms in the Middle East and south-west Asia are the major natural hazards and the Tigris-Euphrates alluvial plain has been recognized as the main dust source in this area. The dust originating from this area can be transported over large distances. Therefore, the dust storms from the Middle East also have important impacts on the neighbouring countries like Iran. The dust activities have intensified in the Mesopotamian areas in recent years, partly due to the development of the dam construction projects on Tigris and Euphrates rivers as well as Karkheh River. The main contribution of this thesis is to assess the hydrologic impact of engineering project in the Karkheh River Basin (KRB) and simulation of hydrologic process in the watershed and its wetland, Al Hawizeh. The first objective of this thesis is to analyse the changes in the landuse/landcover (LULC) over the study area due to the engineering project during 1985-2013 by use of multi-temporal satellite data. In this regard, four Landsat satellite images were selected and corrected prior to accomplishing the main analysis. In this part, the focus of study was to analyse the changes in vegetation and agricultural activities in the KRB. Therefore, a subset of study area in downstream of Karkheh dam which involved the agricultural field was selected for analysis. Supervised Classification was applied on all images and change detection analysis was performed to detect the changes in the LULC. The second objective to study the effect of engineering project in the study area is assessment of land surface temperature (LST) over the study region. Therefore, two Landsat images in the before and after developing dam were selected. For that, Landsat TM5 for 1998 and Landsat ETM+7 for the year 2002 were selected for the analysis of LST in the study area. The third objective of this study is evaluation of wetland shrinkage during 1985 to 2013. To do this, four Landsat Images for the years 1985, 1998, 2002, and 2013 were selected to analyse the shrinkage and change detection. Finally, as fourth objective, simulation of hydrologic process in the KRB and al Hawizeh wetland was performed by Soil and Water Assessment Tools (SWAT). In this regard, we constructed a catchment-based continuous (1987-2010) rainfall–runoff model for the entire KRB watershed (area ~50,760 km2 ) using the SWAT model to understand the natural flow system, and to investigate the impacts of reduced overall flow and the related land cover and landuse change downstream in the wetland. Calibration, validation, and uncertainty analysis were performed using Sequential Uncertainty Fitting Ver. 2 (SUFI2). The calibration periods (1987-1990) and validation period (1991-1994) was selected. The results of calibration and validation are also used to simulate the two downstream flow gauge stations. For this purpose two scenarios were determined for this section, the flow with dam and without dam. Using the calibrated model the annual flow volume (AFV) was calculated for the Karkheh into the wetland throughout the modelled setup for Pay e Pol and Hamidiyeh Stations. The results show that, the LULC in the study area have changed and the agricultural activity in the study area have increased from 5900 ha to 71000 ha due to the construction of engineering project. As LST analysis results, after dam operation, and change LULC in the study area, the overall LST is increased especially near the Al Hawizeh wetland (Hoor al Azim) by 2-7 Kelvin. Additionally, the results obtained from the detection of desiccation in Al Hawizeh wetland shows that the area of wetland decreases dramatically from 3386 to 925 km2 in year 2002. It means that the wetland lost ~73% of its surface area from 1985 to 2002. Finally, by using SWAT model, the model shows that the flows during 1987 to 2000 (before dam construction) and 2001 to 2010 (after dam construction) were significantly reduced after the Karkheh dam construction. The corresponding AFVs for the Hamidiyeh and Pay e pol stations were 8.92×1011 and 1.04×1012 m3 in 1987–2000 and 2.57×1011 to 3.94×1011 m3 in 2001–2010. Thus, the AFVs before and after dam construction were reduced to 6.34×1011 and 6.53×1011 m3 for the Hamidiyeh and Pay e Pol gauges, respectively. Consequently, it is concluded and founded that flow reduction and discharge to the wetland, affected the wetland area, in which the surface area of the wetland was reduced and the risk of dust storm is increased. Using a relationship that describes the impact of reduced AFV on the areal extent of the wetland, it evaluated the impact of additional reductions in flow that will result from the implementation of the planned engineering projects on the Tigris–Euphrates system and Karkheh River over the next few years.